Effect of Heat Treatment on the Formation Cement Stone Microstructure - Sopov, Viktor; Kugaevska, Tatyana; Shulgin, Vladimir; Durachenko, Heorhii (International Journal of Engineering and Technology, 2018)
The influence of temperature on the cement stone structure formation of was investigated. The role of gel and capillary porosity of cement stone in the formation of basic properties of concrete is shown. The regularities of pore structure formation under the influence of the temperature factor are established. The advantage of "soft" heat treatment of modes of hardening concrete is shown for the optimal pore structure formation of cement stone that provides specified properties.
Keywords: capillary pores; cement stone; gel pores; heat treatment; porosity; scanning calorimetry; thermopÐ¾rometry.